Preparation and characterization of fluorophenylboronic acid-functionalized monolithic columns for high affinity capture of cis-diol containing compounds - Li, Qianjin; Lü, Chenchen; Liu, Zhen (Journal of Chromatography A, 2013)
•Three fluorophenylboronic acid-functionalized monoliths were prepared.•The monoliths exhibited untrahigh boronate affinity toward cis-diol compounds.•The boronate affinity was strongly influenced by spacer arm length.•The monolith with appropriate spacer arm length can bind with cis-diols at pH 6.0. Boronic acids are important ligands for the selective recognition and capture of cis-diol containing compounds, such as nucleosides and glycoproteins. In a recent study, it was found that 2,4-difluoro-3-formyl-phenylboronic acid (DFFPBA) exhibited an ultrahigh boronate affinity for binding with monosaccharides. Herein three DFFPBA-functionalized monolithic columns with varying spacer arms were synthesized and characterized. Different cis-diol containing compounds were used for the evaluation of the boronate affinity of the DFFPBA-functionalized monoliths. The DFFPBA-functionalized monoliths exhibited advantageous characteristics. These monoliths exhibited an ultrahigh boronate affinity toward cis-diol containing compounds. Moreover, the monolith with appropriate spacer arm exhibited a low binding pH (6.0) for cis-diols of small molecular weight. These advantages made DFFPBA-functionalized monoliths suitable for the enrichment of trace cis-diol containing compounds in neutral and weak acidic real samples. In addition, it was interesting that the length of spacer arms strongly influenced the boronate affinity: increasing the spacer arm resulted in apparently reduced boronate affinity, and inappropriate spacer arm length even eliminated the boronate affinity toward glycoprotein. To explain such a phenomenon, a possible mechanism was proposed. Finally, the potential of DFFPBA-functionalized monoliths for real applications was demonstrated with the selective enrichment of modified nucleosides from human urine.